Enhancement of p-type gas-sensing performances of NiO nanoparticles prepared by precipitation with RuO2impregnation - V. Kruefu (2018)
In this work, 0-1.00 wt% Ru-loaded nickel oxide nanoparticles were synthesized by the chemical precipitation/impregnation methods and systematically characterized for gas-sensing applications. Characterizations by electron microscopy, X-ray diffractometry, X-ray photoemission spectroscopy showed that primary particles were face-centered-cubic structure of NiO and RuO2nanoparticles were dispersed within larger NiO NPs. Nitrogen adsorption studies also revealed that specific surface area of RuO2/NiO nanoparticles increased with increasing Ru content. Gas-sensing measurement showed that increasing Ru loading content considerably improved C2H5OH response and selectivity against H2S, NO2, SO2, H2, and NH3at an operating temperature of 350 °C. In particular, the NiO sensor with the highest Ru content of 1.00 wt% showed a high p-type sensor response of 35.9-2000 ppm C2H5OH at 350 °C, which was about three times as high as that of unloaded one. Therefore, RuO2loading by impregnation is an effective mean to improve the gas-sensing performances of p-type NiO-based gas sensors.